Pictures, Images, and Conceptual Change - Pitt, Joseph C. author. aut Link
X, 165 p.
Keywords: In this essay I am concerned with the problem of conceptual change. There are, needless to say, many ways to approach the issue. But, as I see it, the problem reduces to showing how present and future systems of thought are the rational extensions of prior ones. This goal may not be attainable. Kuhn, for example, suggests that change is mainly a function of socio-economic pressures (taken broadly). But there are some who believe that a case can be made for the rationality of change, especially in science. Wilfrid Sellars is one of those. While Sellars has developed a full account of the issues involved in solving the problem of conceptual change, he is also a very difficult philosopher to discuss. The difficulty stems from the fact that he is a philosopher in the very best sense of the word. First, he performs the tasks of analyzing alternative views with both finesse and insight, dialectically laying bare the essentials of problems and the inadequacies of previous proposals. Secondly, he is a systematic philosopher. That is, he is concerned to elaborate a system of philosophical thought in the grand tradition stretching from Plato to White head. Now with all of this to his credit, it would appear that there is no difficulty at all, one should simply treat him like all the others, if he indeed follows in the footsteps of past builders of philosophic systems.